2003
DOI: 10.1037/0003-066x.58.6-7.466
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing school-based prevention and youth development through coordinated social, emotional, and academic learning.

Abstract: A comprehensive mission for schools is to educate students to be knowledgeable, responsible, socially skilled, healthy, caring, and contributing citizens. This mission is supported by the growing number of school-based prevention and youth development programs. Yet, the current impact of these programs is limited because of insufficient coordination with other components of school operations and inattention to implementation and evaluation factors necessary for strong program impact and sustainability. Widespr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
961
1
103

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,546 publications
(1,097 citation statements)
references
References 45 publications
32
961
1
103
Order By: Relevance
“…Regression analyses demonstrated that most of these effects were unique (additive), rather than duplicative. This suggests that interventions aimed at promoting ethnic, parent, peer, and school resources might enhance psychological adjustment, with a multipronged program likely to be more efficacious than one that seeks to bolster just one of the resources (Greenberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Regression analyses demonstrated that most of these effects were unique (additive), rather than duplicative. This suggests that interventions aimed at promoting ethnic, parent, peer, and school resources might enhance psychological adjustment, with a multipronged program likely to be more efficacious than one that seeks to bolster just one of the resources (Greenberg et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the social and emotional learning (SEL; Durlak et al 2011;Greenberg et al 2003) theoretical framework emphasizes the importance of building emotional and interpersonal capacities and developing prosocial behavior as a core element in school-based intervention programs. Among several SEL programs, however, the term prosocial is used in a broader perspective because it refers also to positive or competent social behavior.…”
Section: The Promotion Of Prosocial Behaviors In School Settingsmentioning
confidence: 99%
“…Finally, involvement of workers can create space for them to voice their dissatisfaction, if any. Review of literature shows that universal programs can benefi t low-risk as well as high-risk persons (9) and longterm, multi-year and multi-component programs can produce long-term benefi ts (6) . According to the Offi ce of Juvenile Justice and Delinquency Prevention (32) , " identifying programs that have been proven effective is essential to preventing juvenile violence and delinquency " (p.i) and three criteria for " model " violence prevention programs are set.…”
Section: Discussionmentioning
confidence: 99%
“…In a highly developed city like Hong Kong, adolescents are prone to risks like drugs abuse, alcohol and tobacco uses, Internet addiction and school violence (5) . Western countries such as the USA have years of experience in implementing large-scale preventive programs to address adolescents ' developmental problems like the Life Skill Training Program (6) . However, on the contrary, social service agencies in Hong Kong usually focus on remedial interventions rather than preventive measures when handling youth problems.…”
Section: Introductionmentioning
confidence: 99%